3D Printing of Polyvinylidene Fluoride‐Based Piezoelectric Sensors for Noninvasive Continuous Blood Pressure Monitoring - Mandal, Arijit; Morali, Alban; Skorobogatiy, Maksim; Bodkhe, Sampada (Advanced engineering materials, 2024)
The successful fabrication and application of 3D‐printed piezoelectric sensors, made from polyvinylidene fluoride‐barium titanate nanocomposites, for continuous blood pressure (BP) monitoring, is presented. The sensors are fabricated using direct‐ink write 3D printing technique possessing excellent flexibility, rendering them ideal for wearable applications. Key printing parameters, such as nozzle size and pressure, are optimized to achieve a β‐phase of 70% and an overall crystallinity of 48.3%. The sensors are characterized under dynamic pressures and show excellent linearity with a coefficient of determination (R2) of 0.99 and a pressure sensitivity of 0.024 V kPa−1, and demonstrate durability over 3600 cycles. The performance of our piezoelectric sensors is compared with a standard BP monitoring device for a subject, and a strong correlation with a standard deviation of 3.87 and 0.63 mmHg for sytolic BP and diastolic BP, respectively, is found. The development of sensors through 3D printing, as demonstrated in this study, represents a significant scientific advancement in the field of personalized healthcare. This novel approach enables the creation of customized wearable devices tailored for real‐time health monitoring of BP and heart rate. 3D‐printed polyvinylidene fluoride‐barium titanate nanocomposite sensors are optimized, by studying their crystallinity and phase composition. These sensors are tailored for real‐time blood pressure monitoring, and possess a high sensitivity of 0.024 V kPa−1 and excellent linearity. Their applicability in the continuous monitoring of blood pressure and heart rate is demonstrated.